PERISTALTIC FLOW OF PARTICLE-FLUID SUSPENSION IN A CIRCULAR CYLINDRICAL TRACT - BAPPAH, MUHAMMAD AHMADU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2019)
Peristalsis is a form of fluid transport achieved with the aid of progressive, contraction-expansion wavelike movements along the walls of the fluid containing tract (channel/pipe/tube). It appears mostly in biological systems, such as in the ureter, in the intestines and oviducts in the human body. In the study, a particle-fluid suspension is treated as a two-phase fluid and considered to be flowing through a circular cylindrical flow tract, under the influence of a long wave peristaltic flow situation. Two sets of equations, for the fluid phase and the particulate phase, are taken. At the end when the volume fraction of the particulate phase q is made zero, the results did agree, to some extent with the case of a single-phase fluid. From this study therefore it implies that, as long as a Newtonian fluid is assumed, the fluid type may not adversely affect the results, hence may correspond to the single-phase fluid situation.